Solvability of the boundary-value problem for the second-order elliptic differential-operator equation with spectral parameter in the equation and boundary conditions - Aliev, B. A. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
We investigate the solvability of a boundary-value problem for second-order elliptic operator differential equation with a spectral parameter in the equation and boundary conditions. We also study the asymptotic behavior of eigenvalues corresponding to a homogeneous boundary-value problem.